Pengaruh Puasa Daud Terhadap Kejadian Penyakit Tidak Menular (PTM) pada Lansia di Provinsi Gorontalo - Gubali, Sarif S; Ilham, Rosmin; Vonny Lasanuddin, Hamna (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, storke, and heart disease are the leading causes of morbidity and mortalility in the elederly. Efforts to prevent and control NCDs through a healthy lifestyle apporoach, including diet and worship, are gaining increasing attention. The Davie Fast, a from of sunnah fasting perfomend alternately, is believed to have physiological benefits that have the potential to reduce the risk of NCDs in the elderly in Gorontalo Province. Methods : This study used a qualitative study design with an accidental approach. The sample consistend of 15 elderly people aged ?60 years old who were divided into two groups : those who regularly practice the David fast and those who do not. Data was collected through interviews. Data analysis was carried out using the chi-square test and logistic regression to determine the relationship between the practice of David fasting and the incidence of non-communicable diseaases. Results: The results of the study showed that there was a significant influence between the frequency of David fasting and the incidence of non-communicable diseases in the elderly in Gorontalo Province, with a p-value of 0,018. This indicates that the practice of David fasting has an effect on the incidence of non-communicable diseases in the elderly. This fast can be an effective non-pharmacological intervention in the elderly health promotion strategy in Gorontalo Province